2015
DOI: 10.3390/md13052602
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diversity of Anti-Lipopolysaccharide Factor Isoforms in Shrimp and Their Characters Related to Antiviral Activity

Abstract: Anti-lipopolysaccharide factor (ALF) is a small protein with broad-spectrum antimicrobial activity, which has potential application in the disease control. Previously, we isolated seven ALF isoforms from the Chinese shrimp Fenneropenaeus chinensis. In the present study, their distributions in tissues of shrimp were analyzed and the data showed that different isoforms had different expression profiles, which suggested that they might have different functions. Then, the functions of different isoforms were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…The authors incubated WSSV with synthetic domains before injecting the WSSV into the white prawn, Exopalaemon carinicauda, and then quantified the copy number. By substituting other amino acids for lysine, the authors demonstrated that the presence of lysine on the binding domain is essential for inhibiting the replication of the virus (Li et al, 2015). Both studies support the notion that ALF could, indeed, be a candidate antiviral agent but further work needs to undertaken on the exact way by which ALFs interfere with viral replication.…”
Section: Antiviral Defencementioning
confidence: 88%
See 1 more Smart Citation
“…The authors incubated WSSV with synthetic domains before injecting the WSSV into the white prawn, Exopalaemon carinicauda, and then quantified the copy number. By substituting other amino acids for lysine, the authors demonstrated that the presence of lysine on the binding domain is essential for inhibiting the replication of the virus (Li et al, 2015). Both studies support the notion that ALF could, indeed, be a candidate antiviral agent but further work needs to undertaken on the exact way by which ALFs interfere with viral replication.…”
Section: Antiviral Defencementioning
confidence: 88%
“…It is unclear how ALF interacts with WSSV but a plausible explanation might be virus-binding, which would prevent them from attaching and entering their host cell. More recent work by Li et al (2015) tested the inhibitory activity of synthetic lipopolysaccharide binding domains from F. chinensis ALF (Group B) against WSSV. The authors incubated WSSV with synthetic domains before injecting the WSSV into the white prawn, Exopalaemon carinicauda, and then quantified the copy number.…”
Section: Antiviral Defencementioning
confidence: 99%
“…The synthetic loop of the LPS-binding domain from the ALFs of mud crab [8], shrimp [9,11,12], and Indian mud crab [10] inhibit both gram-negative and gram-positive bacteria, while that from the ALF of black tiger shrimp protects hematopoietic cell cultures from white spot syndrome virus infection [23]. Li et al [13] had compared antibacterial and antiviral activities of the LPS-binding domain of seven ALF isoforms from the Chinese shrimp and revealed that an identical Lys residue site was specifically conserved in peptide with antimicrobial activity, suggesting that a certain Lys residue is a key residue in antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the corresponding synthetic LPS-binding domain peptides of anti-LPS factor (ALF) from several crustacean species were shown to exhibit antimicrobial activities [8,9,10,11,12,13]. Lactoferrin is a non-hemic iron-binding glycoprotein with antimicrobial activity via its LPS-binding domain (reviewed by [14]).…”
Section: Introductionmentioning
confidence: 99%
“…The LPS binding domain (LBD) is considered as the functional domain for antimicrobial and antiviral activities [ 23 , 24 ]. Multiple isoforms of LBDs exhibit different antimicrobial activities against either Gram-positive or Gram-negative bacteria [ 25 , 26 ]. The LBD motif of rALF- Pm3 shows a β-hairpin structure with two anti-parallel β-strands linking by a disulfide bond [ 27 ].…”
Section: Introductionmentioning
confidence: 99%